ACCOUNTING AUDITING IN PUBLIC SECTOR INSTITUTIONS - Azadeh barati; Saud Jabbar Muhammad; Saadoun Jabbar Muhammad; Mustafa Habib Naima; Mustafa Taleb Najm (Scholar Express Journals, 2022)
This research shows the importance and role of accounting audit in the public sector, as the public sector consists of large and complex units, and those units are managed by employees who have many different powers and responsibilities in those government units. In order for the wheel of life to proceed regularly within the governmental unit, the interest in different countries has increased towards the accountability of government employees, and this is due to the increasing popular demands and pressure of public opinion, where it is difficult to have an effective and efficient system for government administration centrally and locally without the availability of a kind of popular accounting accountability for which the audit was The government unit to check on it by measuring and evaluating the performance of government unit departments in acquiring resources and allocating them to the goals to be achieved. The research aims to identify the concept of auditing and its role in preserving public money and to identify the rules of professional conduct for auditing accounts and to clarify the standards for the audit profession as well as the statement of the concept of governmental organizations and their characteristics and types. Finally, the concept of governmental auditing and its importance in government units was discussed. As for the research problem, it lies in how government audit affects public sector units. Finally, it is concluded from this research that the audit of accounts is the cornerstone of every institution and the audit of accounts is based on a set of characteristics and information that are considered as the basis for the purpose for which it was developed, and is also based on a set of criteria that guide and give the framework in which it is active. It also concludes that a good government audit leads to the prevention of corruption, fraud and manipulation and works to preserve public money and helps to discover non-economic practices within the government unit. It also shows that auditing the performance of the government unit properly is reflected in improving performance and increasing its efficiency, and thus improving the administrative system within the government unit and producing appropriate information that helps in making appropriate decisions.
Keywords: Accounting audit; government audit; government regulations; accounting accuracy standards.